PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN INDEKS LQ45 TAHUN 2019-2021 - Simanjuntak, Kaleb Yordan; Hasibuan, Henny Triyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023DO - 10.24843/EEB.2023.v12.i09.p03, 2023)
The purpose of this study is to analyze and increase theoretical knowledge regarding the effect of dividend policy, profitability and leverage on firm value. The theory applied in this research is signaling theory and agency theory. The population in this study are companies listed on the LQ45 Index. The sample in this study was obtained from a purposive sampling technique. The data obtained will be analyzed using multiple regression analysis method. The results obtained are dividend policy and profitability have a partial and cumulative positive effect on firm value while leverage has a negative effect on firm value.